PENGEMBANGAN PEMBELAJARAN PETA KONSEP DAN APLIKASI E-LEARNING MOODLE: UPAYA MENINGKATKAN KETUNTASAN BELAJAR DAN SIKAP POSITIF TERHADAP MATEMATIKA SISWA SMK SURAKARTA1) - Henny Ekana Chrisnawati; Ira Kurniawati; Yemi Kuswardi (Universitas Sebelas Maret, 2012)
Abstract This main purpose of this research is developing a mind mapping model of learning with moodle e learning application to increase SMK’s student mathematics achievement and positive attitudes towards of mathematics. In line with the objective of the research, so this research is R and D research model. This research aim to produce a learning devices and research instruments that comply a mind mapping model of learning with moodle e learning application. It used 4D procedur by Thiagarajan that comprised some phase, namely : Define, Design, Develop, and DisseminateThe subject of development research is XH class of SMK Warga Surakarta’s students. The collection data methods, we used achievement test of students, validation sheet of all instruments research , and observation sheet of positives attitudes students of towards mathematics, observation sheet of management classroom by the teacher, students response sheet towards devices and the implementation of learning. To analyze the datas, we used quantitative descriptive analyze. The descriptive analyze used to describe achievement of learning outcomes from validator, that consist of mathemetics achievement, positives attitudes towards mathematics and students responses to mind mapping model of learning with moodle e learning application. The result of this research has been developed the devices of learning and implementation of mind mapping model of learning with moodle e learning application. That is (1) the average of positives attitudes towards mathematics reliabilities is 79.2 %. It means the result of observations made both observers was credible and the instruments had a good category (2) the average of reliabilities of teacher’s abilities to manage his classroom is 84.75 %. It means the result of observations made both observers was credible and the instruments had a good category. (3) the result of respons’s students was unknown thal all aspects were above 70%, exception was an aspect that related by classroom condition (3) the achievement tes that was developed from this research were valid instrument, have reliability indeks 0.77 and the average of sensitive indeks was 0.5051. It means that all instrument of learning can be used. Kata Kunci : pembelajaran peta konsep, aplikasi e learning moodle, sikap positif siswa terhadap matematika, hasil belajar